Comparing Two Improved Techniques With the Traditional Surgical Techniques for Intra and Extramedullary Spinal Tumor Resection: A Report of 280 Cases - Djumanov, Kamaliddin; Kariev, Gayrat; Chmutin, Gennady; Antonov, Gennady; Chmutin, Egor; Musa, Gerald; Maier, Adam; Shumadalova, Alina (Frontiers in Surgery, 2022)
Objectives: This study analyses our experience with the treatment of spinal cord tumors and compares traditional management and a new different surgical approach to intramedullary tumors with an associated hydrosyringomyelia. Materials and methods: This retrospective study compared standard surgical techniques and 2 new improved techniques for intra and extramedullary spinal tumors at our single center. Preoperative neurological status was recorded with the ASIA/ISNCSCI scale. Postoperative outcome was graded using the Nurrick score. Results: Of the 280 cases, there were 220 (78.5%) extramedullary and 60 (21.5%) with intramedullary spinal tumors. The control and main group had 159 (56.8%) and 121 (43.2%) patients respectively. Severe compression myelopathy (ASIA- A, B, C) was 217 (77.5%) patients i.e., ASIA A -39 (13.9%); B-74 (26.4%) and C-104 (37.1%). In 74 extramedullary tumors (33.6%) treated with the new method (IAP24517), good postoperative outcomes in 44 cases (59.5%) with OR = 1.9; 95% CI 1.1 to 3.3 (p<0.05). Thirty-seven (61.7%) intramedullary tumors were treated with the new technique (IAP46698). There was no difference with the standard method (p = 0.15). However, when comparing postoperative Nurick grade 1-2 with grade 3-4, the new method was superior with improvement in 24 (65%) patients, OR = 3.46; 95% CI 1.2 to 10.3 (p<0.05). Conclusion: When compared with standard methods, the proposed newer technique of surgical treatment of spinal cord tumors with the insertion of a syringosubarachnoid shunt in the presence of an associated hydrosyringomyelia is associated with better postoperative outcome (Nurick 1 and 2) in 64.8%.